2007
DOI: 10.1097/01.lgt.0000245049.67965.39
|View full text |Cite
|
Sign up to set email alerts
|

Auditing the Use of Colposcopy Versus General Gynecology Clinics to Investigate Women With Postcoital or Intermenstrual Bleeding

Abstract: Most patients with PCB and IMB will not have a serious abnormality. Our study proposes that a new PCB/IMB outpatient service can improve the efficiency of treatment of these women by providing appropriate guidelines to standardize their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Although most women are asymptomatic, the condition can present with irregular discharge and postcoital and intermenstrual bleeding. 6,7 It has been suggested that cervical ectopy may be a potential risk factor for various sexually transmitted diseases, including Chlamydia trachomatis, 8 HIV, 9 and HPV infection. [10][11][12] In a previous work we showed that the detection of HPV DNA was more common in cervical ectopy than in cytology normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…Although most women are asymptomatic, the condition can present with irregular discharge and postcoital and intermenstrual bleeding. 6,7 It has been suggested that cervical ectopy may be a potential risk factor for various sexually transmitted diseases, including Chlamydia trachomatis, 8 HIV, 9 and HPV infection. [10][11][12] In a previous work we showed that the detection of HPV DNA was more common in cervical ectopy than in cytology normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical relevance of HPV infection in women with cervical ectopy remains unclear as cervical ectopy is not considered a malignant condition. Also, a number of women with cervical ectopy suffer from bothersome symptoms like abundant leucorrhoea, postcoital and intermenstrual bleeding, pelvic pain and recurrent cervicitis, that can impact their quality of life ( Harry et al., 2007 ; Hua et al., 2012 ; Cekmez et al., 2016 ). The presence of chronic symptoms, along with the risk of further infections, warrants treatment of cervical ectopy, mainly cauterization of the area ( Machado et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that all symptomatic women under 65 years and with cervical cancer have PCB (Slater, 1995). Chlamydia infection is the most important cause of PCB in women under 35 years, while for those under 35 years is cervix cancer or endometriosis (Harry et al, 2007). Women with suspicious cervix cancer firstly should undergo clinical examination, if there is evident appearance of tumor only Pap smear test is performed.…”
Section: Introductionmentioning
confidence: 99%